Internet connectivity disruption in Belarus (Belarus) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Belarus. Data sourced from IODA.
Network Disruption Incident ID: BY-2026-1485. Severity: critical. Confidence: 65%